Understand the construct of formative assessment and its role between diagnostic and summative: High school entrepreneurship subjects - Prawinugraha, Azira; Yuliawati, Sri; Sugiarto, Sugiarto (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2024)
This study aims to understand the formative assessment construct for high school entrepreneurship subjects, as well as examine the relationship between diagnostic and summative. Mixed research methods transformative design approach. The first framework is mixed methodology: convergent parallel design combines qualitative interactive model analysis (IMA) techniques and quantitative exploratory factor analysis (EFA) techniques. The second framework is quantitative confirmatory factor analysis (CFA) techniques. The research location was in a cluster of senior high schools in Bintan district. The IMA sample consists of 5 high school entrepreneurship teachers recruited through purposive sampling, while for the EFA and CFA, 259 students were recruited randomly. IMA analyze the understanding and factors involved by teachers in carrying out formative assessments as an important element of learning progress, EFA explores the initial composition of formative assessment constructs, and CFA acts as a lens (affirmation) that evaluates the outer model. EFA forms a fit model. The final interpretation explains that the construct of formative assessment in entrepreneurship subjects has the nature of complementarity, an inner model that moves circularly, repeated interactions produce learning progress, and strengthens the basis of the centrality of formative between diagnostic and summative